Plant metabolite profiles and the buffering capacities of ecosystems. (February 2015) - Fester, Thomas
Abstract : Graphical abstract: Buffering capacities of ecosystems are important properties regarding management and stability. Metabolite profiling of key plant species may be one approach to study such capacities. Highlights: Metabolite profiling may reveal stress buffering capacities of ecosystems. Exogenous and endogenous factors, homeostasis and time scale are key caveats. Stress has a relatively clear metabolic signature even under field conditions. Treatments and replicates have to apply to the plot level for an ecosystem focus. Correlation of metabolite and ecosystem data allows access to buffering mechanisms. Abstract: In spite of some inherent challenges, metabolite profiling is becoming increasingly popular under field conditions. It has been used successfully to address topics like species interactions, connections between growth and chemical stoichiometry or the plant's stress response. Stress exerts a particularly clear impact on plant metabolomes and has become a central topic in many metabolite profiling experiments in the fields. In contrast to phytochambers, however, external stress is often at least partially absorbed by the environment when measuring under field conditions. Such stress-buffering capacities of (agro)-ecosystems are of crucial interest given the ever-increasing anthropogenic impact on ecosystems and this review promotes the idea of using plant metabolite profiles for respective measurements. More specifically I propose to use parameters of the response of key plant species to a given stress treatment as proxies for measuring and comparing stress-buffering capacities of ecosystems. Stress response parameters accessible by metabolite profiling comprise for example the intensity or duration of the impact of stress or the ability of the plant organism to recover from this impact after a given time. Analyses of ecosystem stress-buffering capacities may improve our understanding of how ecosystems cope with stress and may improve our abilities to predict ecosystem changes.